The Efficacy of Anti-Corruption Institutions in Italy. (1st November 2020) - Feldman, Daniel L.
Abstract : The efficacy of an institution must be measured against the challenges it faces. In Italy, anti-corruption institutions face considerable obstacles, including weak national government, strong local loyalties, and deeply-rooted cultural factors. However, in recent years, Italy has made serious and effective efforts to combat corruption. The massive Tangentopoli scandal of 1992 discredited all major political parties in Italy at the time, but also sharply diminished public tolerance of corruption. As a result, Italy finally adopted many of the anti-corruption measures that had long been pressed on it by international treaties and conventions. The creation and gradually increased empowerment of Italy's National Anti-Corruption Authority (ANAC), beginning in 2009, has begun to alter the culture of Italian bureaucracy. Italy's legal system, its Court of Auditors, and its Guardia di Finanza, perhaps in response to competition from ANAC, have also become more energetic in their efforts to fight corruption. While corruption remains a very serious problem, and by some measures has even worsened in some ways, Italy's anti-corruption institutions are not ineffective.